EphA‐Mediated Regulation of Stomatin Expression in Prostate Cancer Cells - Masanari Nishida; Akira Sato; Akio Shimizu; Nor Idayu A. Rahman; Akinori Wada; Susumu Kageyama; Hisakazu Ogita (Cancer Medicine)
ABSTRACT Background and Aims Tumor growth and progression are affected by interactions between tumor cells and stromal cells within the tumor microenvironment. We previously showed that the expression of an integral membrane protein, called stomatin, was increased in cancer cells following their association with stromal cells. Additionally, stomatin impaired the Akt signaling pathway to suppress tumor growth. However, it remains unclear how stomatin expression is regulated. To explore this, we examined the cell surface molecules that can transduce the intercellular communication signals between cancer cells and stromal cells. Results Among these molecules, EphA3 and EphA7 receptors and their ligand ephrin‐A5 were found to be expressed in prostate cancer cells, but not in prostate stromal cells. Cell‐to‐cell contact of prostate cancer cells through the EphA–ephrin‐A interaction suppressed stomatin expression, while knockdown of EphA3/7 or ephrin‐A5 increased stomatin expression. This increase contributed to an inhibition of prostate cancer cell proliferation. Intracellularly, the binding of ephrin‐A to EphA attenuated extracellular signaling‐regulated kinase (ERK) activation that promoted stomatin expression. Furthermore, ELK1 and ELK4, which are Ets family transcription factors phosphorylated by ERK, were involved in the induction of stomatin expression. We also found that higher Gleason score prostate cancer tissue samples had increased activation of EphA, while the stomatin expression and activated ERK and ELK levels were all low. In the mouse xenograft tumor samples generated by implantation of prostate cancer cells, EphA3 phosphorylation was attenuated and the ERK–ELK signaling and stomatin expression were enhanced in the area where stromal cells infiltrated the tumor. Conclusion The EphA‐mediated signaling suppresses the ERK–ELK pathway, leading to the reduction of stomatin expression that affects prostate cancer malignancy.